Epidemiology of injuries in Australian junior rugby league players - Orr, R.; Hamidi, J.; Levy, B.; Halaki, M. (Journal of Science and Medicine in Sport, 2021)
Objectives: Conduct a large-scale epidemiological study of injury characteristics (location, type, mechanism, severity, burden) and incidence in community junior rugby league. Design: Prospective cohort epidemiology study. Methods: Injury surveillance was conducted in three district leagues (Penrith, Canberra, Melbourne) in under 6 (U6) to under 18 years (U18) age groups across the 2016 season. Club sports trainers recorded all match/training medical-attention injuries using a commercial electronic application which recorded injury circumstances and characteristics. Results: A total of 13,169 players from 897 teams participated and 408 (89% male) players sustained 485 injuries, 94% of which were match related. The overall injury incidence was 5.9 injuries/1000 player hours and highest in U13-U18 female players (22.2 injuries/1000 player hours). The mean injury severity of 16 ± 31 days missed training/match-play caused an overall injury burden of 94.2 days missed/1000 player hours). Tackles accounted for 84% of injuries. Joint and contusion injuries were the most prevalent injury type and the head (35% total injuries, primarily bruising and bleeding) was the most injured body site. Conclusions: This is the first study to report injuries across a large cohort of all-age Australian community junior rugby league players over one season. Injury prevalence was lower than previously reported in junior rugby league suggesting the sport has not become more dangerous for junior players. These findings provide an evidence-base to inform or revise policy, training and injury prevention programs and athlete development pathways in relation to game-wide safety and develop best-practice protocols in injury management for rugby league athlete support personnel.